Identification Of Ecotherapy Design Criteria In Public Open Spaces As An Effort To Improve Visitor’s Mental Health - Prasandya, Km. Deddy Endra; Satria, Made Wina; Adiartha, Made Arya (Politeknik Internasional Bali, 2023)
All activities that occur in public open spaces are basically forms of human expression as social beings who always have a deep relationship with the environment in meeting physical, psychological and social needs. Referring to mental health, the role of public open space is very important nowadays considering the number of teenagers with mental disorders in Indonesia, especially in Bali is very high. The role of public open spaces in improving the mental health of visitors is needed to reduce the prevalence of depression. The concept of ecotherapy in public open spaces can be implemented to promote mental health through human interaction with green spaces. This study aims to formulate ecotherapy design criteria in public open spaces and find out the design elements of public open spaces in Denpasar City and Klungkung Regency that need to be adjusted to be able to implement the ecotherapy concept. A synthesis of various ecotherapy theories and the link between public open spaces and mental health, as well as various studies or studies that have been conducted previously were carried out to formulate ecotherapy design indicators and sub-indicators in public open spaces. The research method used is mixed methods, by applying qualitative and quantitative approaches. The results of the study concluded that the two public open spaces which are the objects of study need to adjust the accessibility criteria, location, zoning, parking, furniture, facilities, and sign systems.